Spontaneous pneumomediastinum, Hamman syndrome: case report - Luilson Geraldo Coelho Júnior; Estevão Tavares de Figueiredo; Cristian Machado Haesbaert (Medicina, 2016)
Pneumomediastinum is defined as free air or gas within the mediastinum, and in case of spontaneous pneumomediastinum there is no evidence of trauma, invasive procedures or previously diagnosed lung diseases. Spontaneous emphysema is a rare condition at urgent care centers. Hammam’s syndrome or spontaneous pneumomediastinum is more frequent in young adults. The more frequent symptoms are chest pain and dyspnea. Hammam’s sign, a pathognomonic sign of mediastinal emphysema, is a crunching, rasping sound, synchronous with heartbeat, heard over the precordium. Pneumomediastinum is diagnosed with the aid of chest X-rays and chest CT scans. It is usually a benign self-limited condition. Treatment is conservative and symptom alleviating. The purpose of this study was to describe a case of Hammam’s syndrome and the importance of clinical evaluation and early diagnosis of this disease